Economic efficiency and risk of cassava farming in Lampung province - Zulkarnain Zulkarnain; Wan Abbas Zakaria; Dwi Haryono; Ktut Murniati (Goodwood Publishing, 2021)
Purpose: This study aimed to analyze the effect of the use of production factors on cassava production, to analyze cassava income, to analyze the level of economic efficiency in the use of cassava production factors, and to analyze the risk of cassava farming in Lampung Province. Research methodology: The population consisted of 473 farmers from TerusanNunyai, Central Lampung regency. Interviews, observation, documentation, and questionnaires were all used to collect data. Results: The performance of cassava farming which is measured based on the income analysis, the average income value is Rp. 7.351.369,66 with an R/C ratio of 1,46. Then, production factors for NPK-Phonska, TSP/SP-36, KCL, manure, labor, pesticide, and land are not economically efficient in cassava farming, while seed production factors are not economically efficient yet. Income and production in cassava farming have a high risk. Limitations: There is unavoidable transaction cost; therefore, it is necessary to involve transaction costs to get the maximum profit to reach economic efficiency. Contribution: The contribution of this research is to provide input for cassava farmers to get maximum income by avoiding the slightest possible risk.